Quality management in Quantity Surveying firms - Tan, Chin Keng; Johari, Sazila; Yeoh, Kah Ching (2016)
Quality management in Quantity Surveying firms is vital to ensure the standard of services provided by the firms. Nevertheless, limited literatures on issues and problems in relation to the practices of quality management in the firms found. The objectives of this research are to identify the problems of quality management in Quantity Surveying firms and to determine the strategies to overcome the problems of quality management in the firms. The method of questionnaire survey was applied to collect data for this research. 129 sets of questionnaire were distributed. 32 sets of completed questionnaire were received from the respondents for data analysis. The findings conclude that the major problems of quality management in Quantity Surveying firms are lack of systematic documentation procedures for quality management, lack of systematic coordination procedures for quality management, and lack of exposure on quality management system among staff. As for the strategies to overcome the problems, this research suggests the following strategies, i.e. promote a quality working environment, enhanced supervision from senior QS, quality award from the management to the staff, provide regular training conducted by the top management, and training of internal quality audit for all staff.